제주마의 기본모색과 MC1R과 ASIP 유전자형 조합의 상관관계 - 김남영; 한상현; 이성수; 이종언; 박남건; 고문석; 양영훈; Kim, Nam-Young; Han, Sang-Hyun; Lee, Sung-Soo; Lee, Chong-Eon; Park, Nam-Geon; et al. (Journal of animal science and technology, 2011)
This study was undertaken to reveal the relationship between genetic variations and the basic coat color classification system in Jeju horses. Genetic variations of the melanocortinreceptor 1 (MC1R) and agouti signaling protein (ASIP) genes were investigated using pyrosequencing technique. A nucleotide substitution mutation for MC1R g.901C>T and an ASIP 11-bp deletion mutation were screened. Black horses had MC1R $E^+$/- ($E^+/E^+$ or $E^+/E^e$) and ASIP $A^a/A^a$ genotypes. In contrast, chestnut horse genotypes were MC1R $E^e/E^e$ and ASIP -/-. Thus, black and bay horses have at least one dominant MC1R allele, $E^+$, whereas chestnut horses have homozygous recessive alleles $E^e/E^e$. This suggests that the MC1R genotypes determine chestnut or black/bay coat color, regardless of the genotype distribution of ASIP. In addition, the horses with MC1R $E^+$/- and a dominant ASIP $A^A$/- allele showed bay coat color, but not black, suggesting that the ASIP $A^A$ allele represses black coat color development in the hairs of the body, but not in the mane and all four legs. Pedigree analysis showed a consistent relationship between the genotype distribution of the MC1R and ASIP genes and basic coat color patterns, even in the $F_1$ progeny. The results of this study revealed the relationship between the coat color phenotype and genetic background and suggested that useful information may be provided for molecular breeding of Jeju horses. 본 연구는 제주마의 기본모색 분류체계와 유전 변이간의 관계를 확인하기 위해 수행되었다. pyrosequencing 방법을 이용하여 melanocortin receptor 1 (MC1R)과 agouti signaling protein (ASIP) 유전자의 변이를 분석하였다. MC1R은 g.901C>T 염기치환을 분석하였고, ASIP는 11-bp 결실돌연변이를 분석하였다. 가라마필은 MC1R에서는 $E^+$/- ($E^+/E^+$ or $E^+/E^e$), ASIP에서는 $A^a/A^a$ 유전자형이 나타났다. 유마 마필에서는 MC1R은 $E^+$/- 그리고 ASIP는 $A^A$/- 유전자형이 나타났다. 반면에 적다 마필에서 MC1R은 $E^e/E^e$ 유전자형만이 나타났으며, ASIP에서는 모든 조합의 유전자형이 나타났다. 가라모색과 유마모색은 MC1R에서 적어도 1개의 $E^+$ 우성대립유전자를 갖고 있어야하며, 적다모색에서는 동형열성대립유전자인 $E^e/E^e$ 유전자형을 가져야 한다. 이는 ASIP 유전자형 분포와 관계없이 MC1R 유전자형에 의해 가라/유마모색과 적다모색을 결정하는 것이다. 또한 MC1R은 $E^+$/- 그리고 ASIP은 우성대립유전자인 $A^A$/-를 갖는 마필은 유마모색을 나타내는데 이는 ASIP은 우성대립유전자인 $A^A$에 의해 사지를 제외한 부분에서 흑모색발현을 억제하는 것으로 추정된다. 가계분석에서는 제주마와 더러브렛간에 교배로 생산된 $F_1$ 자마의 기본모색 양상과 MC1R 및 ASIP 유전자형 분포와의 관계에 대해 일정한 결과를 보여주고 있다. 본 결과는 모색에 대한 표현형과 유전양상 간의 관계를 보여주고 있으며, 제주마의 분자육종을 위한 중요한 정보를 제공할 수 있을 것으로 사료된다.